Distance From Nest and Climate Explain Geographical Trends of Harvester Ant's Food Resource Use: A Multi‐Species Approach - Diego Anjos; Pedro Luna; Kleber Del‐Claro; Rodrigo G. Pol; Javier Lopez de Casenave; Helena Maura Torezan‐Silingardi; Martha L. Baena; Florencia Baudino; Judie Bronstein; Melissa Burt; Eduardo Calixto; Ana Laura Cao; et al. (Journal of Biogeography, 2025)
Main Animals not only forage for abundant and nearby resources, but their diets can also be influenced by abiotic and geographic factors. This often results in non‐random interactions among species. We investigate how seed density, distance from nest, abiotic (e.g., climate stability, temperature, precipitation) and geographic factors (e.g., latitude, elevation and continental hemisphere) influence the removal of food items (i.e., seeds and dead arthropods) by Pogonomyrmex species. Location South and North America, from Patagonia to the Rocky Mountains. Taxon Genus Pogonomyrmex (Formicidae: Hymenoptera). Methods Conducting standardised experiments, we performed a seed removal experiment and an assessment of the items retrieved by ant workers of 160 nests from eight Pogonomyrmex spp. at 16 sites extending the American continent. Results Pogonomyrmex ants native to North America removed more seeds than their South American counterpart. In general, results align with optimal foraging theory, indicating a higher probability of seed removal near ant nests. High climate stability correlated with lower seed predation rates, emphasising seed consumption's significance in historically arid environments. Increased precipitation and temperature led to reduced removal of food resources, suggesting reduced water availability and lower mean temperatures increases the consumption of seeds by harvester ants. Conclusions Overall, Pogonomyrmex ants' food resource use is influenced by a combination of factors such as region, distance from the nest and climate. This study underscores harvester ants' potential impact on plant distribution over large spatial scales consuming seeds from the immediate proximity of their nest and preventing establishment.

Tradeoffs in longleaf pine conservation: Prescribed fire management increases exotic ambrosia beetle abundance in pine-hardwood forests - Davide Nardi; Hannah Bares; Natalie A. Clay; Robin Verble; Davide Rassati; Lorenzo Marini; John Thomason; John J. Riggins (Forest Ecology and Management, 2024)

Ant functional structure and diversity changes along a post-grazing succession in Mediterranean oak woodlands - Clara Frasconi Wendt; Alice Nunes; Melanie Köbel; Robin Verble; Paula Matos; Mário Boieiro; Cristina Branquinho (Agroforestry Systems, 2021)